Ghosts in the machine beliefs, values and worldviews in the workplace and business environment - Baker, Christopher 1961-; Power, Maria (2018)
This paper analyses the role and impact of beliefs, values and worldviews (BVW) in the business and work-based environment, and how they are translated and negotiated in non-spiritual and non-sacred spaces. Based on pilot research with a cohort of English Roman Catholic employees and managers conducted within a retreat setting, and as part of a wider research project across religious and non-religious cohorts, the article traces an emerging framework identifying the different variables informing the relationship between BVW and public workplace settings. These variables include: how material structures of the workplace are shaped by the ethical and moral teachings generated by BVW; the close links between BVW (also known as spiritual capital) and agency in the business and work environment; the overlapping but also contrasting relationship between religious and non-religious BVW; and innovative and resilient forms of leadership and change management strategy generated by the reflective prioritising of BVW within these contexts.
Keywords: Beliefs; Roman Catholic; Leadership; Spiritual Capital; values and worldviews; Workplace